Environmental impact of the Southern Peru Copper Corporation Mining Company in Latin America: A historical approach from the Early 20th Century to the present - Pérez-Jiménez, Sol (Revista Geográfica de América Central., 2018)
Despite the recognition that it was from the 90s and the imposition of neoliberal regulations that there was a drastic increase in mining extraction in Latin America, the transnational mining in the region has its antecedents since the beginning of XX century. The paper reviews this phenomenon through the history of one of the most important mining companies of the time, the American Mining and Smelting Company (Asarco), today a subsidiary of the mining company Grupo México. It started operating in Peru since 1921 and, since then, it has expanded its presence in the region and has remained one of the world's leading copper producers. The work describes how all this has involved numerous social conflicts and strong environmental impacts reported since the mid-twentieth century and perpetuated to this day. Finally, it is questioned whether these business and industrial practices should continue to be reproduced in a context of high environmental conflicts, lack of resources and climate change.